Extraction Kinetics and Reaction Rates of Sacred Lotus Stamen Tea Infusion-Derived Flavonoids in Relation with Its Antioxidant Capacity - Tungmunnithum D. (2023)
Stamen tea from Nelumbo nucifera Gaertn. (or the so-called sacred lotus) is widely consumed, and its flavonoids provide various human health benefits. The method used for tea preparation for consumption, namely the infusion time, may affect the levels of extractable flavonoids, ultimately affecting their biological effects. To date, there is no report on this critical information. Thus, this study aims to determine the kinetics of solid liquid extraction of flavonoid from sacred lotus stamen using the traditional method of preparing sacred lotus stamen tea. Phytochemical composition was also analyzed using high-performance liquid chromatography (HPLC). The antioxidant potential of stamen tea was also determined. The results indicated that the infusion time critically affects the concentrations of flavonoids and the antioxidant capacity of sacred lotus stamen tea, with a minimum infusion time of 5–12 min being required to release the different flavonoids from the tea. The extraction was modeled using second order kinetics. The rate of release was investigated by the glycosylation pattern, with flavonoid diglycosides, e.g., rutin and Kae-3-Rob, being released faster than flavonoid monoglycosides. The antioxidant activity was also highly correlated with flavonoid levels during infusion. Taken together, data obtained here underline that, among others, the infusion time should be considered for the experimental design of future epidemiological studies and/or clinical trials to reach the highest health benefits.